2001
DOI: 10.1021/ma001437u
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Polyampholytes to Charged Surfaces

Abstract: The adsorption of flexible polyampholytes to charged surfaces has been investigated. The electrostatic interactions are included in a mean-field manner, while the chain connectivity is treated by Metropolis Monte Carlo (MC) simulations. For large enough surface charge densities, adsorption is found both for neutral polyampholytes and for polyampholytes carrying the same net charge as the surfaces. The simulation results are used to check the reliability of previously proposed analytical theories. The exponents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…The particle size was also found an important parameter for large particles, where the surface becomes large enough to adsorb the whole amphoteric chain. Concerning a planar charged surface instead of a spherical particle, several groups 35,36 found results that confirm experimental and theoretical data; i.e., the PA adsorption occurs when the local attraction with the surface becomes stronger than the net charge repulsion. Consequently, short PA chains remain in bulk while chain entropy is stronger than chain polarizability, and the adsorption process increases with the PA length, PA block size, and surface charge.…”
Section: Introductionsupporting
confidence: 55%
“…The particle size was also found an important parameter for large particles, where the surface becomes large enough to adsorb the whole amphoteric chain. Concerning a planar charged surface instead of a spherical particle, several groups 35,36 found results that confirm experimental and theoretical data; i.e., the PA adsorption occurs when the local attraction with the surface becomes stronger than the net charge repulsion. Consequently, short PA chains remain in bulk while chain entropy is stronger than chain polarizability, and the adsorption process increases with the PA length, PA block size, and surface charge.…”
Section: Introductionsupporting
confidence: 55%
“…Setting the cutoff at the Gaussian chain size actually eliminates all chains that are in the strongly stretched pole regime. This was done in the Monte Carlo simulations conducted by Khan et al128 As a result of this selection method, the authors observe a weak chain size dependence on the degree of polymerization in the pole regime, D ∼ N 0.7 . This weak dependence is not surprising because the selected cutoff eliminated all strongly polarized chains for which the chain size scales with number of monomers N as D ∼ N 1.5 .…”
Section: Polarization‐induced Attraction and Polyampholyte Adsorptionmentioning
confidence: 99%
“…[1][2][3][4][5] Adsorption of polyelectrolytes on charged surfaces is one of the classical problems of the physical chemistry of polymers, the theoretical basis of which was developed only in the last decade. [6][7][8][9][10][11][12] The mechanism of polyampholyte adsorption described by Dobrynin et al [7] is based on a polarization of macromolecular chains in the electric field created by a charged object. For a single macromolecular chain, three adsorption regimes on the plane having s charges per unit area are postulated to occur.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Neyret et al [16] and Berre et al [17] observed a redistribution of amphoteric chain segments, with positively charged segments concentrated in the inner negatively charged interfacial zone, and negatively charged segments concentrated far from the oppositely charged surface. The theory of polyampholyte adsorption on charged surfaces [6][7][8][9][10][11][12][18][19][20] was successful in interpreting additional experimental results on the adsorption of synthetic polyampholytes on charged polystyrene latex, [21,22] mica and silica particles, [23,24] and fibers. [25][26][27] Colloidal systems such as latex particles have an extremely large interfacial area and represent attractive candidates for the purification of proteins from a biological mixture.…”
Section: Adsorption Of Polyampholytes At the Interfacesmentioning
confidence: 99%